(untitled) (Globalization and Business, 2018)
The report describes the long-term evolution of human physical strength and capabilities on the background of global technological progress. To illustrate their interrelation, rele- vant graphs were created for the long-term historical period, namely, 1700-2050 years. It turned out that the global change in human physical use is evolutionary and, also, has a regressive tendency. Global technological development has the opposite, i.e. the progressive tendency, which is revolution- ary. The use of statistical and qualitative analysis has shown that there is a negative correlation between the use of physi- cal capabilities and global technological progress in the longer term (i.e. in the trend of the century).